Optimization Model for Refinery Hydrogen Networks Part II - Tarifa, Enrique Eduardo (2016)
In the first part of this work, a model of optimization was presented that minimizes the consumption of the hydrogen of a refinery. In this second part, the model will be augmented to take into account the length of the pipelines, the addition of purification units and the installation of new compressors, all features of industrial real networks. The model developed was implemented in the LINGO software environment. For data input and results output, an Excel spreadsheet was developed that interfaces with LINGO. The model is currently beingused in YPFLuján de Cuyo refinery (Mendoza, Argentina).